Intrafractional vaginal dilation in anal cancer patients undergoing pelvic radiotherapy (DILANA): a prospective, randomized, 2-armed phase-II-trial - Arians, Nathalie; Häfner, Matthias; Krisam, Johannes; Uzun-Lang, Kristin; Wark, Antje; Körber, Stefan A.; Hommertgen, Adriane; Debus, Jürgen (BMC cancer, 2020)
The incidence of anal cancer is rising in the last decades and more women are affected than men. The prognosis after chemoradiation is very good with complete remission rates of 80-90%. Thus, reducing therapy-related toxicities and improving quality of life are of high importance. With the development of new radiotherapy techniques like IMRT (Intensity-modulated radiotherapy), the incidence of acute and chronic gastrointestinal toxicities has already been reduced. However, especially in female anal cancer patients genital toxicities like vaginal fibrosis and stenosis are of great relevance, too. Up to now, there are no prospective data reporting incidence rates, techniques of prevention or impact on quality of life. The aim of the DILANA trial is to evaluate the incidence and grade of vaginal fibrosis, to optimize radiotherapy by reducing dose to the vaginal wall to minimize genital toxicities and improve quality of life of anal cancer patients.
Gesehen am 30.03.2020